Isolation and characterization of a broad-spectrum phage of multiple drug resistant Salmonella and its therapeutic utility in mice. (January 2019) - Tang, Fang; Zhang, Peng; Zhang, Qingmei; Xue, Feng; Ren, Jianluan; Sun, Jianhe; Qu, Zhina; Zhuge, Xiangkai; Li, Dezhi; Wang, Juanfang; Jiang, Min; Dai, Jianjun
Abstract: Salmonella are causes of livestock, poultry, and other animal diseases but they also have the potential to infect people. Currently, antibiotics are the first choice for treatment of Salmonella infections. Thus, the utility of phage has become the research focus for scientists for several reasons. There are efficient, non-toxic, ubiquitous, easy to prepare and can result in the lysis of host bacteria. In this study, a broad spectrum bacteriophage of Salmonella was isolated from the fecal samples of a poultryfarm and we studied the morphological aspects, thermal stability, pH stability, optimal multiplicity of infection (MOI), and one-step growth curve of this phage. This phage was named Salmonella phage SaFB14 and lysed 54.12%(105/194) Salmonella spp. SaFB14 belongs to the Siphoviridae and has a polyhedron head with a diameter approximating 60 × 60 nm and a tail approximating 140 nm. The optimum growth temperature was 37 °C and maintained high activity over a widepH range(pH3-10) with an optimum of pH 7.0. The optimal MOI was 0.1. A one-step growth curve showed that its latency time was 10 min, burst time was 70 min, and burst was 23 particles. In order to study the therapeutic effect of phage SaFB14 in infected mice, mice were challenged with 2 × 10 9 CFU/mouse Salmonella (cs20130523-001-1). Each mouse was injected to 2 × 10 10 PFU SaFB14 1 h later. SaFB14 protected 40% of mice from infection. Then, the same dose of phage was given to mice for 3 days continuously. After 3 days treatment, the survival rate increased to 60%.In conclusion, phage SaFB14 showed wide host range and good activity in vivo, it is promising against diseases caused by Salmonella . Highlights: SaFB14 is a broad spectrum bacteriophage of Salmonella. Phage SaFB14 maintained high activity over a wide pH range. Phage SaFB14 protected 60% of mice from Salmonella Enteritidis infection after 3 days treatment.